GAMIFICATION OF EDUCATIONAL PRACTICE (ON THE EXAMPLE OF THE EXPERIMENT OF A GROUP OF PARENTS ON FAMILY EDUCATION IN CHEBOKSARY) - Никитина, Александра Валерьевна (Bulletin of the Chuvash State Pedagogical University named after I Y Yakovlev, 2021)
Рассмотрено понятие «геймификация» и его значение для сферы образования. Разведены понятия «геймификация» и «игровое обучение». Представлены направления, по которым велась трансформация систем обучения через принятие принципов геймдизайна в эксперименте группы родителей по семейному обучению в г. Чебоксары: обучение через получение опыта (учителя не дают готовых ответов, а предлагают для решения задачи и проблемы на основе комплекса дисциплин), осуществление контроля посредством древа навыков (визуально представленной разветвленной карты развития ученика, которая предполагает самостоятельный выбор направления развития тех или иных его умений и навыков), конструирование методики преподавания дисциплин с учетом жанровой специфики видеоигр (игры-действия, симуляторы, стратегии, ролевые игры, приключения, головоломки), специфический дизайн учебного класса (через соотношение приватной и публичной зон). Описаны положительные и отрицательные эффекты внедрения данных направлений: повышение мотивации, прозрачность в оценивании задач, стремление к развитию, точечное решение проблем ребенка, связанных с его коммуникативными и познавательными навыками; возникновение внутренних конфликтов, связанных с получением знания через опыт, постоянное внимание со стороны учителя, тьютора и психолога. The article considers the concept of gamification and its significance for the sphere of education; differentiates the concepts of gamification and game learning; provides the areas of transformation of training systems through teaching the principles of game design in a family learning group in Cheboksary: learning through experience (teachers do not give answers, but offer some tasks and problems through a set of disciplines), control through the skill tree (a skill tree is a visual branched map of the student’s development, which assumes an independent choice of the area of development of his skills and abilities), the design of disciplines, taking into account the genre of video games (games, simulations, strategies, role-playing games, adventures, puzzles), the specific design of the classroom (through the ratio of private and public zones). The article also describes positive and negative effects of the introduction of these orientations: increased motivation, transparency in the assessment of tasks, the desire for development, the point solution of the child’s problems associated with his communication and cognitive skills; the emergence of internal interactions associated with the acquisition of knowledge through experience, constant attention from the teacher, tutor and psychologist.